2022
DOI: 10.3390/v14050949
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Neuroimaging Findings in Severe COVID-19 Patients with Initial Neurological Impairment: An Observational Study

Abstract: Background and Objectives: Cerebral complications related to the COVID-19 were documented by brain MRIs during the acute phase. The purpose of the present study was to describe the evolution of these neuroimaging findings (MRI and FDG-PET/CT) and describe the neurocognitive outcomes of these patients. Methods: During the first wave of the COVID-19 outbreak between March 1 and May 31, 2020, 112 consecutive COVID-19 patients with neurologic manifestations underwent a brain MRI at Strasbourg University hospitals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…The short- and long-term functional outcome of patients with severe COVID-19 and brain perfusion abnormalities needs to be further investigated. However, a recently published follow-up of patients with COVID-19 and initial neurological symptoms 42 , of whom 68% had MRI abnormalities (including perfusion abnormalities), shows that nearly half of them had persistent slightly diminished results in working memory and executive functions testing. Alteration of such frontal neurocognitive functions might have a link with the fronto-temporal pattern of hypoperfusion that we report.…”
Section: Discussionmentioning
confidence: 99%
“…The short- and long-term functional outcome of patients with severe COVID-19 and brain perfusion abnormalities needs to be further investigated. However, a recently published follow-up of patients with COVID-19 and initial neurological symptoms 42 , of whom 68% had MRI abnormalities (including perfusion abnormalities), shows that nearly half of them had persistent slightly diminished results in working memory and executive functions testing. Alteration of such frontal neurocognitive functions might have a link with the fronto-temporal pattern of hypoperfusion that we report.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Others have found that after severe COVID, gray matter volume decreases. 8 After mild COVID infection, some authors found no gray matter abnormalities at all. 12 Most quantitative MRI studies investigating the period following COVID-19 infection have found abnormalities in structures associated with the olfactory system.…”
mentioning
confidence: 99%
“…Therefore, it is particularly important to detect or refute the central nervous system effects of the SARS-CoV-2 virus in people who have experienced mild COVID-19.In patients with severe COVID-19 requiring intensive care unit treatment, conventional MRI techniques sometimes detect brain abnormalities during and after acute infection: microbleeds, ischemic lesions, and white matter abnormalities have been reported. 8 However, no clear central nervous system abnormalities underlying long COVID have yet been detected by conventional MRI. 9 The results of quantitative MRI studies looking for subtle differences-not visible by direct visual analysis-are surprisingly contradictory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These alterations are a result of ischemic strokes and changes in structural white matter integrity. 1,3 Nonetheless, these sequences cannot detect biomarkers associated with the neurological symptoms observed in mild COVID patients. 4 Previous studies have performed morphometric gray matter approaches.…”
mentioning
confidence: 99%